BRCA-analyzer: Automatic workflow for processing NGS reads of BRCA1 and BRCA2 genes. (December 2018) - Kechin, Andrey; Khrapov, Evgeniy; Boyarskikh, Uljana; Kel, Alexander; Filipenko, Maxim
Graphical abstract: Highlights: BRCA-analyzer is an automatic workflow for the processing of BRCA1/2 genes NGS data. BRCA-analyzer has variant filters adapted to amplicon-based targeted NGS data. BRCA-analyzer includes a new Python-script for annotation with BIC database data. BRCA-analyzer was tested on 899 samples of patients with three different cancers. BRCA-analyzer can be used to identify germline as well as somatic mutations. Abstract: The use of targeted next-generation sequencing (NGS) provides great new opportunities for molecular and medical genetics. However, in order to take advantage of these opportunities, we need to have reliable tools for extracting the necessary information from the huge amount of data generated by NGS. Here we present our automatic multithreaded workflow for processing NGS data of BRCA1 and BRCA2 genes obtained with NGS technology named BRCA-analyzer. Optimizing it on the sequencing data of 899 samples from 693 patients, we were able to find the most reliable tools and adjust their parameters in such a way that all pathogenic variants found were confirmed by Sanger's sequencing. For 82 and 24 DNA samples from blood and formalin-fixed paraffin-embedded blocks, NGS libraries were prepared with GeneRead BRCA panel v2 (Qiagen). The reads obtained were processed with BRCA-analyzer and Qiagen GeneRead Data analysis workflow. In total 27 pathogenic variants were found and confirmed by Sanger's sequencing, with all of them determined with BRCA-analyzer. Qiagen GeneRead Data analysis discarded 5 true pathogenic variants due to their location in homopolymeric sequence stretches. For other 793 samples, libraries were prepared by the in-house method, and NGS data were analyzed by BRCA-analyzer in comparison to another free automatic amplicon NGS workflow Canary. From total 137 pathogenic variations, BRCA-analyzer found 135 and Canary 123. Mutations were missed by BRCA-analyzer due to the trimming primer sequences from reads before mapping to be fixed in the next version. On the freely available NGS data, we showed that BRCA-analyzer could also be used for hybrid capture gene panels, although it needs more extensive testing on such library preparation methods. Thus, BRCA-analyzer is an automatic workflow for processing NGS data of BRCA1/2 genes with variant filters adapted to amplicon-based targeted NGS data. BRCA-analyzer can be used to identify germline as well as somatic mutations. BRCA-analyzer is freely available athttps://github.com/aakechin/BRCA-analyzer .